Chemokines gene expression in the prefrontal cortex of depressed suicide victims and normal control subjects - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Bhaumik, Runa; Zhang, Hui (Brain, behavior, and immunity, 2021)
•We found chemokines abnormalities in postmortem brain of depressed suicide subjects.•We found decreased mRNA levels of several chemokines in the brain of depressed suicide subjects.•We found decreased mRNA of CXCL1, CXCL2, CXCL3, and CCL2 in postmortem brain of depressed suicides.•Brain chemokines abnormalities may be involved in the pathophysiology of depression and suicide. Abnormalities of neuroinflammation have been implicated in the pathogenesis of depression and suicide. This is primarily based on the observation that cytokines, which are major inflammatory molecules and play an important role in depression and suicide, are increased in both serum and in postmortem brain of depressed and suicidal subjects. Another class of immune mediators are chemokines which are primarily involved in chemotactic properties and trafficking of immune cells in the central nervous system (CNS). Chemokines also play an important role in CNS function. Whereas chemokines have been studied in the serum of depressed and suicidal patients, their role in brain of depressed or suicidal subjects is relatively unexplored. We studied the gene expression of several chemokines in the prefrontal cortex (PFC) obtained from depressed suicidal (DS) and normal control (NC) subjects. We determined the mRNA expression of several chemokines belonging to CXCL and CCL groups of chemokines using qPCR array technique and qPCR gene expression validation in 24 DS and 24 NC subjects. The postmortem brain samples were obtained from the Maryland Brain Collection. We found that the mRNA expression of chemokines CXCL1, CXCL2, CXCL3 and CCL2 was significantly decreased in the PFC of DS compared with NC subjects. No significant change was observed in CXCL5, CXCL6, CXCL10, CCL8 and CCL19 between DS and NC subjects. Since many of the chemokines are involved in mediating certain important CNS functions, such as neurotrophic effect, neurogenesis, anti-apoptotic growth factor release, modulation of synaptic transmission, brain development and neuronal loss, decreased levels of chemokines can reduce these functions which may be involved in the pathophysiology of depression.